GETTING TO KNOW BLOCKCHAIN TECHNOLOGY AND ITS ROLE IN COMPUTER DATA SECURITY - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
Blockchain technology, with its decentralized architecture and underlying cryptography, offers a solution to secure and protect data more effectively than conventional systems. Every transaction recorded on a blockchain is first verified by a network of nodes together before it can be carried out, making surreptitious modification of data almost impossible. In addition, the cryptographic security features of the blockchain ensure that only interested parties can access the data, and the transparent transaction records can facilitate the audit process to be more precise and accurate. However, the implementation of blockchain technology is also faced with various obstacles. Issues such as capacity, data privacy, and regulation are the main challenges that need to be overcome to enable its wider adoption. Technical complexities and a lack of public understanding of the technology are also slowing down its acceptance in various industry sectors. Therefore, this research recommends a hybrid approach that combines traditional and blockchain technologies to create a more comprehensive and resilient data security solution.